IN A SIX - MONTH LONGITUDINAL INVESTIGATION, BOTH THE MEDICAL AND DENTAL PROFESSIONS OBSERVED INDIVIDUALS WITH POST - COVID VACCINATION SYMPTOMS - Dr Navpreet Singh, Dr Manvir Singh, Dr Anshul ,( Dr Hardik Pahuja, Dr Harnoor Singh Sandhu, Dr Avineet Kaur, (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
The objective of the study is to observe individuals with post - covid vaccination symptoms in a six - month longitudinal investigation, both the medical and dental professions. Material and Method A questionnaire based cross sectional study was conducted by enrolling the individuals with post - covid vaccination symptoms in a six - month longitudinal investigation, by both the medical and dental professions during the period from 10 November 2021 to 10 January 2022 . Results. Most common side effects were fever, muscle pain, lack of appetite, and nausea, whereas anaphylactic reactions were more common after the first dose. Long-term post-covid vaccination consequences were detected in patients, including Pneumonia 10, ARDS 4, Multi-organ failure 7, and others 9. Males were more susceptible to covid vaccine symptoms following vaccination, and senior citizens were most afflicted, followed by those of medium age. Conclusion Assessing the safety, efficacy and side effects of the vaccine is urgently needed. Most common side effects were fever, muscle pain, lack of appetite, and nausea. Anaphylactic reactions were more common after the first dose. Long-term post-covid vaccination consequences were detected in patients, including Pneumonia 10, ARDS 4, Multi-organ failure 7, and others 9. We anticipate that our findings will convince the public that vaccinations are safe and worthwhile. Additionally, you can aid in decreasing vaccine hesitancy among people who are concerned about vaccine safety and potential bad effects. Keywords Covid Vaccine, Post covid symptoms , Longitudinal, Medical Dental professionals